2022
DOI: 10.3390/plants11212840
|View full text |Cite
|
Sign up to set email alerts
|

Pre- or Post-Harvest Treatment with MeJA Improves Post-Harvest Storage of Lemon Fruit by Stimulating the Antioxidant System and Alleviating Chilling Injury

Abstract: Cold storage preserves lemon fruit quality; however, it can result in significant chilling injury (CI). The effects of pre- and post-harvest methyl jasmonate (MeJA) treatments at four concentrations (0, 0.1, 0.3, and 0.5 mM) on CI and sensory quality of lemons during 80 d of storage at 7 °C–10 °C were investigated. Both pre- and post-harvest MeJA treatments reduced CI, weight loss (WL) and maintained higher firmness, total soluble solids (TSS), and total acidity (TA) than in the controls. Antioxidant enzyme ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…In this study, along with the storage period, the TSS and soluble sugar content increased and decreased, while MeJA treatment depicted a higher content than CK. These findings also coincide with lemon fruit (Liao et al, 2022), which might be due to the carbohydrate metabolism. Another important effect of cold stress on fruit is the abnormal cell wall metabolism, where the pectin fractions are located, which finally leads to the change in fruit texture.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, along with the storage period, the TSS and soluble sugar content increased and decreased, while MeJA treatment depicted a higher content than CK. These findings also coincide with lemon fruit (Liao et al, 2022), which might be due to the carbohydrate metabolism. Another important effect of cold stress on fruit is the abnormal cell wall metabolism, where the pectin fractions are located, which finally leads to the change in fruit texture.…”
Section: Discussionsupporting
confidence: 77%
“…Studies have shown that JA regulates MAPK activity and MAPK gene expression. Studies have shown that MeJA can enhance the resistance of plants to abiotic stress by increasing the activity of antioxidant enzymes [ 125 ]. MeJA strongly induced 14 CmMAPKs in melon [ 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although cold injury may occur in pitaya stored at temperatures lower than 5 • C, cold stimulation treatment prior to storage can effectively maintain the metabolic balance, inhibit cold injury, and prolong the storage period [34]. Postharvest preservation techniques such as heat stress, phytohormones, and climate-controlled storage can also delay the degree of cold injury to the fruit [35]. In breeding new varieties of pitaya, genetic engineering techniques can be used to manipulate cold-resistance-related genes and improve the fruit's cold tolerance at the genetic level.…”
Section: Cold Injurymentioning
confidence: 99%